Guillain-Barré Syndrome in a 16-Year-Old Male Patient with a Parasitic Infection and Obesity - Wira Mondana; Eva Miranda Fitri; Minarni Eka Dewi; Azizul Berlyansah; Audita Natasya Br. Batu Bara (Program Studi Kedokteran Fakultas Kedokteran Universitas Malikussaleh, 2026)
Guillain-Barré Syndrome (GBS) is an acute immune-mediated polyradiculoneuropathy that is generally preceded by an infection. Although bacterial and viral triggers are well known, the contribution of parasitic infections and metabolic factors remains poorly understood. Case Report: A 16-year-old male presented with acute watery diarrhea for one week, followed by progressive ascending weakness in the lower and upper extremities. The patient also reported a history of intestinal worm infection and had received pyrantel pamoate therapy. Neurological examination revealed symmetrical flaccid weakness with diminished reflexes. Laboratory and radiological examinations ruled out alternative diagnoses. Guillain-Barré Syndrome was clinically diagnosed, and the patient was treated with intravenous immunoglobulin (IVIG) and supportive care in the pediatric intensive care unit. Gradual neurological improvement was observed without respiratory complications. Discussion: This case illustrates the classic post-infectious presentation of SGB while highlighting a potentially underrecognized context—helminthic infection and obesity—both of which may contribute to immune dysregulation. Conclusion: GBS should be considered in patients with progressive weakness following a gastrointestinal illness. The coexistence of parasitic infection and obesity may represent a multifactorial immunological background that warrants further investigation.